Formulation development, manufacture and evaluation of hydralazine hydrochloride microspheres - Kangausaru, Shakemore Tinashe (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Despite improvements in its detection and treatment since the 1970s, hypertension is the most common and important risk factor for cardiovascular diseases. Hypertension is a chronic condition often underdiagnosed and/or inadequately treated in Sub-Saharan Africa. Recent survey results illustrate that the condition continues to contribute significantly to mortality and morbidity in adults and that it is poorly controlled in clinical practice. Hydralazine (HYD) is used either alone or in combination for the management of chronic hypertension, chronic cardiac failure and hypertensive crises. Due to its short plasma half-life of between 2 to 4 hours, HYD is normally administered two to four times daily, therefore making it a potential candidate for inclusion in sustained release formulations. The formulation of sustained release microsphere dosage forms may be useful to improve patient adherence and to achieve predictable and optimised therapeutic plasma concentrations. A stability indicating reversed-phase high performance liquid chromatography (RP-HPLC) method for the quantitation of HYD in pharmaceutical dosage forms was developed and optimised using a Central Composite Design (CCD) approach. UV/Vis detection method was selected as HYD contains an ultraviolet light-absorbing chromophore. The method was validated with respect to linearity and range, limits of quantitation (LOQ) and detection (LOD), accuracy, precision, sensitivity, selectivity and specificity as per International Conference on Harmonisation (ICH) guidelines. The method was applied to commercially available HYD tablets. No interfering peaks were observed from excipients used in the commercially available tablets. Preformulation studies were conducted to ensure the manufacture of high quality, stable sustained release HYD microspheres. The results revealed that there was an interaction between HYD and Carbopol® 971P, therefore Carbopol® polymers were not included during formulation studies. HYD was found to be compatible with Methocel® K100LV, Eudragit® RS PO and Avicel® 101 and HYD formulations were developed and optimised using these excipients. An oil-in-oil (o/o) solvent evaporation technique was selected for the manufacture of HYD microspheres due to its simplicity and to avoid exposure of HYD to moisture that could have been encountered if a water-in-oil (w/o) manufacturing process was used. The selection of o/o solvent evaporation technique was also based on the hydrophilicity of HYD and the polymers selected. Different grades of Methocel® and Eudragit® were selected to evaluate their effect on encapsulation efficiency (EE), in vitro release and microparticle shape and morphology. The best combination of these polymers which resulted in the desired EE, in vitro release, microparticle shape and size were then selected for formulation optimisation. A numerical optimisation approach was used to predict a formulation composition that would produce minimal HYD release initially and maximum HYD release after 12 hours of dissolution testing. The release kinetics of HYD from the manufactured microspheres were established by fitting in vitro release data to several mathematical models. The in vitro release data for the optimised formulations was best described using Higuchi model. The short-term stability of the optimised formulations was established by undertaking stability studies at 4°C, 25 °C/60 % RH and 40 °C/75 % RH. The results revealed that there was no significant change in appearance and physicochemical properties of the microspheres over a period of one month. However, long-term stability studies would be required to determine the shelf-life of the formulations. In addition, a gas chromatographic (GC) method was selected for determining residual amounts of acetone and n-hexane in the optimised formulations. GC methods were developed and optimised by evaluation of process parameters. System suitability testing was performed with respect to resolution, theoretical number of plates and selectivity. Method validation was performed with respect to linearity, range, inter- and intra-day precision, retention time (Rt) precision, limit of quantitation (LOQ) and detection (LOD). A solvent extraction method was used to analyse residual solvents in the optimised formulations. The drying process was sufficient in evaporating acetone and n-hexane from the optimised formulations. Solvent evaporation technique has been successfully used in the manufacture of HYD microspheres. The microspheres have potential for further development, scale up formulation studies and long-term stability studies.
Keywords: Hydralazine; Microspheres; Drugs -- Controlled release; Drugs -- Design; Drug development; Hypertension -- Chemotherapy